2022
DOI: 10.3390/brainsci12040509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weight Loss on Cognitive Functions: A Pilot Study of a Multidisciplinary Intervention Program for Obesity Treatment

Abstract: There is a relationship between obesity and cognitive functioning. Our aim was to assess weight loss influence on global cognition and executive functioning (EF) in adults with obesity under a multidisciplinary weight loss program. In this six-month longitudinal study, we assessed 81 adults (age < 50 years) with body mass index (BMI) ≥ 30. EF and global cognitive performance were evaluated with the Montreal Cognitive Assessment (MoCA), Neuropsychological Battery of Executive Functions (BANFE-2) and Trail Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…In a longitudinal study encompassing 6401 middle-aged adults aged between 39 and 63 years, cognitive decline, as measured by the global cognition score, was notably more pronounced among individuals classified as obese, in comparison to their normal-weight counterparts [54]. Conversely, when investigating the impact of weight loss on global cognition in obese adults participating in a comprehensive multidisciplinary weight reduction program, it was observed that the magnitude of weight loss did not exhibit a significant correlation with cognitive improvement [55]. These findings are in concordance with our own study results, which suggest that the potential cognitive benefits attributed to Zn supplementation are independent of weight loss.…”
Section: Discussionmentioning
confidence: 93%
“…In a longitudinal study encompassing 6401 middle-aged adults aged between 39 and 63 years, cognitive decline, as measured by the global cognition score, was notably more pronounced among individuals classified as obese, in comparison to their normal-weight counterparts [54]. Conversely, when investigating the impact of weight loss on global cognition in obese adults participating in a comprehensive multidisciplinary weight reduction program, it was observed that the magnitude of weight loss did not exhibit a significant correlation with cognitive improvement [55]. These findings are in concordance with our own study results, which suggest that the potential cognitive benefits attributed to Zn supplementation are independent of weight loss.…”
Section: Discussionmentioning
confidence: 93%